2009
DOI: 10.1016/j.jjcc.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Positive remodeling is associated with more plaque vulnerability and higher frequency of plaque prolapse accompanied with post-procedural cardiac enzyme elevation compared with intermediate/negative remodeling in patients with acute myocardial infarction

Abstract: AMI patients with PR have more plaque vulnerability and higher frequency of plaque prolapse accompanied by post-procedural cardiac enzyme elevation compared with AMI patients with IR/NR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, compared with negative remodeling, culprit lesion positive remodeling in ACS was associated with a higher rate of adverse cardiac events. Acute myocardial infarction (AMI) patients with culprit lesion positive remodeling had more plaque vulnerability and higher frequency of plaque prolapse accompanied by post-procedural cardiac enzyme elevation than patients with negative remodeling [ 53 ]. During the long term follow-up, both target lesion revascularization (TLR) and non-TLR rates were significantly higher in ACS patients with positive remodeling than in those with negative remodeling [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with negative remodeling, culprit lesion positive remodeling in ACS was associated with a higher rate of adverse cardiac events. Acute myocardial infarction (AMI) patients with culprit lesion positive remodeling had more plaque vulnerability and higher frequency of plaque prolapse accompanied by post-procedural cardiac enzyme elevation than patients with negative remodeling [ 53 ]. During the long term follow-up, both target lesion revascularization (TLR) and non-TLR rates were significantly higher in ACS patients with positive remodeling than in those with negative remodeling [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…iMAP-IVUS not only allows online delineation of tissue components for each category, but also provides realtime 40 MHz high-resolution gray-scale images, which are also fundamentally important. Most previous intra-coronary tissue classification studies employed VH-IVUS, in which gray-scale resolution is only 20 MHz [6,[20][21][22][23]. 2D analysis has the same limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al 20) reported that ultrasound attenuation with a longitudinal length of ≥5 mm and plaque rupture correlated with no-reflow phenomenon in patients with STEMI. Our previous study 37) showed that positive remodeling, plaque rupture, IVUS-detected thrombus, and tissue prolapse were independently associated with post-stenting cardiac-specific troponin I elevation. In another previous study, 38) we demonstrated that tissue prolapse, high-sensitivity CRP, and culprit lesion multiple plaque ruptures were associated with post-PCI no-reflow in AMI patients with plaque rupture.…”
Section: Post-percutaneous Coronary Intervention Intravascular Ultrasmentioning
confidence: 93%